Hindrance of the Proteolytic Activity of Neutrophil-Derived Serine Proteases by Serine Protease Inhibitors as a Management of Cardiovascular Diseases and Chronic Inflammation - Burster, Timo; Mustafa, Zhadyra; Myrzakhmetova, Dinara; Zhanapiya, Anuar; Zimecki, Michal (Frontiers in Chemistry, 2021)
During inflammation neutrophils become activated and segregate neutrophil serine proteases (NSPs) to the surrounding environment in order to support a natural immune defense. However, an excess of proteolytic activity of NSPs can cause many complications, such as cardiovascular diseases and chronic inflammatory disorders, which will be elucidated on a biochemical and immunological level. The application of selective serine protease inhibitors is the logical consequence in the management of the indicated comorbidities and will be summarized in this briefing.